The Dynamics and Effectiveness of Domestic Violence Law in Indonesia: (Law No. 23 of 2004 on the elimination of domestic violence) - Dyah Syifa Herawati (Dauliyah: Journal of Islam and International Affairs, 2024)
Cases of domestic violence in Indonesia are still relatively high, even though it is known that the law governing it has existed since 2004. Then how are the main objectives that the law wants to achieve in dealing with cases of domestic violence and its effectiveness. In this literature review, researchers used a normative descriptive method supported by data in the form of books, journals, and other relevant research. The result is that the main purpose of the PKDRT law is to maintain the integrity of a harmonious and prosperous household, this is not in line with the sanctions given so that it has a negative impact on the perpetrators and victims who both have family relationships. Then another effort that is more in line with this law is restorative justice with certain considerations. Restorative justice is an implementation of past Islamic law that has been exemplified by the Prophet and his companions. Meanwhile, according to its effectiveness, Indonesian society has not effectively implemented this PKDRT Law due to a weak legal culture and legal awareness.